Preparation and Characterization of a Chloroperoxidase-like Catalytic Antibody - Wang, Fengyang (Molecular Diversity Preservation International (MDPI), 2007)
The small molecule, meso-tetra(α,α,α,α-o-phenylacetamidophenyl) porphyrin (Mr1147.0) was used as complete antigen to elicit MAb through the immunization and cell fusion techniques. The MAb 1F2 obtained was demonstrated to be very pure by MALDI/TOFMS. The subtype of MAb 1F2 is IgG2a, which has a relative molecular weight of 156,678.8 Da.No significant change in the intensity of absorption peaks in UV and CD spectra was observed over a pH range between 6 and 12. The high stability of the abzyme and the tight binding between Fe porphyrin and antibody were also demonstrated. Vmax, Km, κcat, κcat/Km for abzyme are 5.18 × 10−8 Ms−1, 1.50 × 10−8 M, 0.518 s−1, 3.45 × 107 M−1s−1, respectively. The data obtained indicate that catalytic antibody has high catalytic activity. The chloroperoxidase activity of MAb 1F2-Fe porphyrin complex is stable from 10 °C to 60 °C.